Nutrition Education in the Australian New South Wales Primary School Curriculum: Knowledge and Attitudes of Students and Parents - Nienke de Vlieger; Jolien van Rossum; Nicholas Riley; Andrew Miller; Clare Collins; Tamara Bucher (MDPI AG, 2020)
In NSW, Australia, the views of primary-school aged children and their parents in regard to the importance of nutrition education at school are unclear. The aim of the current study was to explore children's knowledge of nutrition and eating habits and to identify gaps that future school nutrition education programs could target. Students aged 9 to 12 years and their parents (n = 21 dyads) were invited to participate in semi-structured interviews, complete a nutrition knowledge questionnaire, and perform a "healthy-unhealthy" food sorting task in a University food laboratory. Among the children, nutrition knowledge scores concerning "serves & portions" of common foods were lowest, identifying a gap in knowledge related to portion size. All children categorized fruits, vegetables, cola, and water correctly as "healthy" or "unhealthy" in the sorting task, but not for the sausage and muesli bar, suggesting that further support categorising processed foods may be needed. The interviews indicated that parents do actively try to teach their children about nutrition, although they reported feeling uncertain about their own level of nutrition knowledge. Children and parents indicated that there is very little nutrition education in school and more is needed. This research could be used to inform future curriculum components related to nutrition education for primary school children.